Efektivitas Program Trans Banten dalam Mendukung Pembangunan Transportasi Publik di Kota Serang - Anggi Yulia; Laeli Nur Khanifah; Farita Kaila; Safira Natasya; Naila Indriyani (Lembaga Pengembangan Kinerja Dosen, 2026)
This research aims to analyze the effectiveness of the Trans Banten Program in supporting the development of public transportation in Serang City. The research uses qualitative methods with a case study approach. Data was collected through observation, interviews, documentation and literature study, then analyzed interactively. The research results show that the Trans Banten Program is quite effective in increasing community accessibility and mobility, especially towards areas of education, government and public services. This service also provides economic benefits through reduced transportation costs and is supported by facilities that are relatively comfortable and safe for users. In addition, the increase in the number of passengers shows the public's acceptance and need for public transportation. However, the effectiveness of the program is not yet optimal because there are still obstacles in the form of fleet limitations, inaccurate operational schedules, passenger density during peak hours, and limited service information. Therefore, it is necessary to improve service quality, add fleets, and strengthen information systems to support the sustainability and optimization of the Trans Banten Program as public transportation in Serang City.